Age-specific effects of early daycare on children's health - Mara Barschkett (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
Over the past decades, the share of very young children in daycare has increased significantly in many OECD countries, including Germany. Despite the relevance of child health for child development and later life success, the effect of early daycare attendance on health has received little attention in the economic literature. In this study, I investigate the impact of a large daycare expansion in Germany on children's age-specific mental and physical health outcomes. Based on a unique set of administrative health records covering 90% of the German population over a period of ten years, I exploit exogenous variation in daycare attendance induced by the expansion. My results provide evidence for the substitution of illness spells from the first years of elementary school to the first years of daycare. Specifically, I find that early daycare attendance increases the prevalence of respiratory and infectious diseases and healthcare consumption when entering daycare (1-2 years) by 5-6 percent. At elementary school age (6-10 years), the prevalence decreases by similar magnitudes. I do not find evidence for an effect of daycare attendance on mental disorders, obesity, injuries, vision problems, or healthcare costs. Heterogeneity analysis indicates more pronounced effects for children from disadvantaged areas, earlier detection of vision problems, and a reduction in obesity in these children.
Keywords: I10; I12; J13; C23; 330; child care; daycare expansion; physical health; mental health; education; administrative health records; difference-in-differences; event study